2013
DOI: 10.1016/j.jand.2012.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Positive Attitudes toward Organic, Local, and Sustainable Foods Are Associated with Higher Dietary Quality among Young Adults

Abstract: Scant evidence is available on the relationship between preferences for organic, local, sustainable, and non-processed foods (i.e., alternative food production practices) and dietary quality. This cross-sectional study examined the characteristics and dietary behaviors (e.g., consumption of fruit, vegetables, fast food, etc.) of young adults who reported placing low, moderate, or high importance on alternative food production practices. A diverse sample of 1,201 students at a two-year community college and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 33 publications
7
120
2
3
Order By: Relevance
“…It is important to highlight that, as showed by many studies, there is also a lack of knowledge and confusion regarding the concept of sustainable food choices and the corresponding logos and labelling (Grunert et al 2013;Pelletier et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that, as showed by many studies, there is also a lack of knowledge and confusion regarding the concept of sustainable food choices and the corresponding logos and labelling (Grunert et al 2013;Pelletier et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, these domains were identified as the most salient for healthy eating among a college population. 10,11,16 “Conscientious” shopping has been associated with healthier diets, 11 while on-/near-campus shopping has been associated with less healthy diets, among college students. 10 In addition, access to supermarkets compared to convenience stores, tend to be associated with healthier diets.…”
Section: Methodsmentioning
confidence: 99%
“…16 For many of the food shopping items, test-retest and/or construct validity have been established in previous research. 11,1720 …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies associated more supportive attitudes towards local food in elderly respondents living in rural areas (Racine et al 2013, Megicks et al 2012, MirosaLawson 2012, Khan-Prior 2010, Tregear-Ness 2005, Brown 2003, Wolf 1997, with women generally exhibiting more positive attitudes than men (Cholette et al 2013, Pelletier et al 2013, Cranfield 2012, Bellows et al 2010). Notably Chambers et al (2007) 'could not identify any differences in attitudes between urban and rural consumers' (Feldmann-Hamm 2015: 156).…”
Section: Introductionmentioning
confidence: 91%